2023
DOI: 10.1007/s00431-023-05100-2
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in patients with Fontan physiology: a systematic review

Rubens J. van den Berg,
Jayanti N. Pos,
Linda E. Scheffers
et al.

Abstract: Fontan circulation is a highly abnormal circulatory state that may affect various organ systems. The effect on body composition is an important factor to assess the condition of the patient. This systematic review assesses body composition and possibly related adverse outcomes in patients with a Fontan circulation, to provide an overview of current insights. Studies evaluating body composition by compartment (either fat mass or lean/muscle mass) in Fontan patients published up to April 2023 were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Furthermore, it has been suggested that creatinine‐based eGFR methods would overestimate mGFR in patients with a Fontan circulation because of its reliance on skeletal muscle mass, 28 , 29 which is known to be reduced in these patients. 32 Cystatin C–based methods have been proposed to circumvent this issue; however, the applicable equations designed for the pediatric and adolescent demographic only became available after our study's enrollment phase. 33 Consequently, these measurements were not available in our data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that creatinine‐based eGFR methods would overestimate mGFR in patients with a Fontan circulation because of its reliance on skeletal muscle mass, 28 , 29 which is known to be reduced in these patients. 32 Cystatin C–based methods have been proposed to circumvent this issue; however, the applicable equations designed for the pediatric and adolescent demographic only became available after our study's enrollment phase. 33 Consequently, these measurements were not available in our data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Low exercise tolerance and sarcopenia are major factors contributing to morbidity and quality of life in patients with total cavopulmonary connection (TCPC) [1][2][3]. Many macroscopic and metabolic changes in skeletal muscle are observed in patients with univentricular circulation.…”
Section: Introductionmentioning
confidence: 99%